Bibliometrics and university libraries: Adding to the professional profile? - Iribarren-Maestro, Isabel (Anuario ThinkEPI, 2018)
The creation of bibliometric services within university libraries opens up new professional possibilities for libraries, when they are in the midst of rethinking many of their functions. Services to the researcher, such as supporting the management of their curricula vitae through CRIS (current research information system), finding quality measures of journals, or providing advice during the evaluation processes, along with elaborating bibliometric reports in order to support the governance of the University, are postulated as new tasks that can be carried out by the library staff. For these new tasks to be effective, librarians must have some transversal and specific competences. Moreover, they need some of the skills associated with communication competences, because of the importance of communicating properly the work that has been done by the Unit, within the library and for the users and institution.
Keywords: University library; Bibliometric services; Library services; Professional development; Research support.